TIES BETWEEN THE RUSSIAN ORTHODOX AND ARMENIAN APOSTOLIC CHURCHES IN RUSSIAN HISTORIOGRAPHY: TRENDS, ACHIEVEMENTS, PROBLEMS - Blohin, Vladimir Sergeevic (History, Archeology and Ethnography of the Caucasus, 2023)
The article examines the issues of relations between the Russian Orthodox and Armenian Apostolic Churches in Russian historiography. The methodology is based on classical and modern approaches to the analysis of historiographic sources. The foundation of the Russian Armenian Studies was laid in the 1830s-1850s with the appearance of historical essays, which contained information on the history of Armenia and Armenian communities (including the activities of Armenian dioceses) in Russia. Later, the first scientific works devoted to a comparative analysis of the Armenian and Orthodox dogmas were published. During the Soviet period, the emphasis was mainly put on studying the history of the Armenian diaspora in Russia. However, the Moscow Theological Academy in 1950-1991 reviewed dissertations, the authors of which explored the history and doctrine of the Armenian Church, including its ties with the Russian Orthodox Church. The undeniable achievements of modern historiography include the study of certain aspects of Russian-Armenian church relations, mainly related to the imperial period. The only scientific work where the subject of study is Russian-Armenian interfaith relations in the Middle Ages is the monograph by K.V. Ayvazyan (1989). The first attempt to compile the events related to the ties between the Russian and Armenian churches in the 20th century belongs to the Armenian clergyman V. Hovannisyan (2005). The question of the exact periodization of Russian-Armenian church relations, the analysis of other trends (besides those mentioned above) have not yet been considered in the domestic scientific historical literature, which makes this topic an urgent historiographic issue.